Skrining Fitokimia, Formulasi, dan Karakteristik Fisik Sediaan Soothing Gel Daging Daun Lidah Buaya (Aloe vera (L.) Burm.f.) - Rosalinda Mahdalena Sinaga; Minda Sari Lubis; Gabena Indrayani Dalimunthe; Yayuk Putri Rahayu (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2023)
The content of aloe vera (Aloe vera (L.) Burm.f.) can make the skin not dry quickly and feel moisturised. Soothing gel is a preparation that works effectively to restore skin moisture, provide comfort and a cooling effect on red and irritated skin so that the skin condition returns to normal and prevents skin dryness. The study aimed to determine the various secondary metabolites in aloe vera leaf flesh, to determine differences in concentrations of aloe vera leaf flesh in soothing gel preparations on the physical characteristics of the practices and to determine material changes before and after stability tests were carried out using the cycling test method. The research method was used experimental, with the independent variables varying the aloe vera leaf flesh concentration 0% (blank), 1%, 2%, and 3%, and the dependent variable secondary metabolites and physical characteristics. The sample preparation method is wet sorting, and other methods used are phytochemical screening, viscometry, and cycling tests. The results of the phytochemical screening showed that aloe vera leaf flesh contains secondary metabolites of flavonoids, glycosides, tannins, saponins, and steroids. The results of the soothing gel formulation with variations in the aloe vera leaf flesh concentration of 0%, 1%, 2%, and 3% showed differences in colour, distinctive aroma, consistency, spreadability, adhesion, pH, and viscosity that met the requirements. The stability test results using the cycling test method showed physical changes in consistency, spreadability, adhesion, pH, and viscosity. However, these changes still met the requirements for good gel preparation according to SNI 16-4399-1996.